Analysis of Student Satisfaction Levels with Online Learning Systems - Hazriyanti, Irma; Mutathahirin, Mutathahirin; Khairunnisa, Khairunnisa (International Journal of Multidisciplinary Research of Higher Education, 2020)
This research aims to analyze student satisfaction in online learning. This research uses quantitative methods. The data source was taken using a questionnaire from 50 active students attending college in a few Universities in Sumatra. All data is then analyzed using software SPSS Windows Version 20 and found 33 students stated that they were not satisfied with the total percentage of 60%, 3 students stated that they were very dissatisfied with the results percentage 5.5% of students, 17 students stated that they were satisfied with a percentage of 30.9 students, then 2 students stated that they were very satisfied with the online learning system with a percentage of 4%. The satisfaction in question is measured through five indicators, namely; i). level of satisfaction, ii) clarity of structure and subject matter of material discussion, iii) suitability of learning material with RPS, iv) consistency of lecturers in online learning, v) liking online learning. The five indicators used as instrument items in this research were used to determine the level of student satisfaction with the online learning system during the Covid-19 pandemic.